Teacher Strategies in Instilling the Values of Tolerance And Diversity in Islamic Elementary Schools - Puspitasari, Nimas; Makmur, Makmur; Munawati, Siti; Nugroho, Arya Setya; Maksum, Hafidh (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze teacher strategies in instilling the values of tolerance and diversity at Sekolah Dasar Islam Multi Plus Ar-Rahiim, Kajangan, East Ungaran. In the context of Islamic elementary education, fostering tolerance and respect for differences serves as a fundamental foundation for developing students’ noble character, openness, and appreciation for social and cultural diversity within Indonesia’s multicultural society. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, five teachers, and five students, as well as through classroom observations and documentation. Data analysis was conducted through the stages of data reduction, presentation, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings reveal that teachers implement several strategies to instill tolerance and diversity, including the integration of multicultural values into classroom learning, habituation through extracurricular and religious activities, and modeling exemplary behavior in daily interactions. Furthermore, the supportive school environment and active parental involvement play a crucial role in strengthening the internalization of tolerance among students. The study concludes that value-based multicultural education in Islamic elementary schools can serve as an effective medium for cultivating tolerant attitudes and a love for diversity from an early age. These findings are expected to serve as a model for developing character education grounded in multicultural values in other Islamic elementary schools.